Air pollution control in the European Community : implementation of the EC directives in the twelve member states - Bennett, Graham (International environmental law and policy series, 1991)
Conclusions (s. 197-200).
Keywords: EY-direktiivi; ilmansuojelu : EY-maat; lakien yhdenmukaistaminen; päästöt; ympäristöoikeus; EY-oikeuden kansallinen voimaansaattaminen